The Impacts of Carbon Emissions and Energy Consumption on Life Satisfaction: Evidence From China - Li, Jiaying; Chen, Fuzhong (Frontiers in Environmental Science, 2022)
This study investigates how carbon emissions and energy consumption related to the life satisfaction of Chinese households over the 2010 to 2018 period. The China Family Panel Studies (CFPS) data from 25 Chinese provinces shows that the effect of provincial carbon emissions on life satisfaction is positive, and increases in fuel and electricity consumption also predict a higher life satisfaction level. Fuel consumption, especially, has a greater impact on life satisfaction among older people with lower income or education levels. In addition, an increase in relative energy consumption negatively affects Chinese households’ life satisfaction. Heterogeneity analysis demonstrates that the relative fuel consumption change has a larger life satisfaction effect for older and less educated people. In developed regions (including Beijing and Shanghai), a strong inverse relationship between carbon emissions and the residents’ life satisfaction exists in China, but the effects of residents’ own and relative energy consumption are insignificant or slight.